2013
DOI: 10.1177/1052562913488108
|View full text |Cite
|
Sign up to set email alerts
|

Narcissism, Materialism, and Environmental Ethics in Business Students

Abstract: We investigate the relationships between narcissism, materialism, and environmental ethics in undergraduate business students. Data were collected from business students (n = 405) at an Association to Advance Collegiate Schools of Business-accredited business school at a comprehensive state university. Results indicate that narcissism has an indirect effect on business students' environmental ethics. Narcissism was significantly related to materialism, and materialism was significantly related to lower levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
20

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 62 publications
(77 reference statements)
2
32
0
20
Order By: Relevance
“…In an interesting simulation looking at usage of a common resource (a renewable forest in this case), Campbell et al (2005) found that those with higher narcissism scores were more likely to select short-term personal gain even at the expense of long-term depletion. Such inferences suggest that the social and environmental costs of narcissism may be high (Bergman et al, 2013).…”
Section: Narcissism Tourism and Sustainability Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…In an interesting simulation looking at usage of a common resource (a renewable forest in this case), Campbell et al (2005) found that those with higher narcissism scores were more likely to select short-term personal gain even at the expense of long-term depletion. Such inferences suggest that the social and environmental costs of narcissism may be high (Bergman et al, 2013).…”
Section: Narcissism Tourism and Sustainability Challengesmentioning
confidence: 99%
“…Bergman et al, 2013). Naderi and Strutton (2014, p. 387) conclude with the proposal that environmentalists should view the struggle to persuade, cajole or seduce inherently and deeply self-interested consumers through new marketing lenses which can manipulate narcissists' self-absorbed tendencies in ways that ultimately benefit the environment and society.…”
Section: Narcissism Tourism and Sustainability Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our behavior is shaped by our thoughts. Any efficient environmental policy needs collectiveness and religious and ethical support (9). Islam, Judaism, Christianity, Zoroastrianism, as the divine religions respect the nature and the entire universe as the creature of God and mandate believers not to destruct or destroy this God gift.…”
Section: Importance Of Spiritual Approach In Promoting Environmental mentioning
confidence: 99%
“…Inclusive, a literatura sugere que as empresas tenham gestores mais responsáveis em relação aos impactos que suas decisões podem causar sobre o meio ambiente (ZHU;CHEN, 2015). Neste contexto, o ensino superior pode desempenhar um papel importante no ensino de práticas de negócios sustentáveis (BERGMAN et al, 2014). As instituições de ensino superior têm como tarefa discernir a verdade, transmitir valores e socializar os alunos a contribuir para o progresso social e o avanço do conhecimento, portanto, tem a responsabilidade de transmitir a visão moral e conhecimento técnico necessário para garantir uma alta qualidade de vida para as gerações futuras.…”
Section: Introductionunclassified